The association between cannabis use and outcome in pharmacological treatment for opioid use disorder - Tea Rosic; Raveena Kapoor; Balpreet Panesar; Leen Naji; Darren B. Chai; Nitika Sanger; David C. Marsh; Andrew Worster; Lehana Thabane; Zainab Samaan (BMC, 2021)
Abstract Background With the ongoing opioid crisis and policy changes regarding legalization of cannabis occurring around the world, it is necessary to consider cannabis use in the context of opioid use disorder (OUD) and its treatment. We aimed to examine (1) past-month cannabis use in patients with OUD, (2) self-reported cannabis-related side effects and craving, and (3) the association between specific characteristics of cannabis use and opioid use during treatment in cannabis users. Methods Participants receiving pharmacological treatment for OUD (n = 2315) were recruited from community-based addiction treatment clinics in Ontario, Canada, and provided information on past-month cannabis use (self-report). Participants were followed for 3 months with routine urine drug screens in order to assess opioid use during treatment. We used logistic regression analysis to explore (1) the association between any cannabis use and opioid use during treatment, and (2) amongst cannabis-users, specific cannabis use characteristics associated with opioid use. Qualitative methods were used to examine responses to the question: "What effect does marijuana have on your treatment?". Results Past-month cannabis use was reported by 51% of participants (n = 1178). Any cannabis use compared to non-use was not associated with opioid use (OR = 1.03, 95% CI 0.87-1.23, p = 0.703). Amongst cannabis users, nearly 70% reported daily use, and half reported experiencing cannabis-related side effects, with the most common side effects being slower thought process (26.2%) and lack of motivation (17.3%). For cannabis users, daily cannabis use was associated with lower odds of opioid use, when compared  with occasional use (OR = 0.61, 95% CI 0.47-0.79, p < 0.001) as was older age of onset of cannabis use (OR = 0.97, 95% CI 0.94, 0.99, p = 0.032), and reporting cannabis-related side effects (OR = 0.67, 95% CI 0.51, 0.85, p = 0.001). Altogether, 75% of cannabis users perceived no impact of cannabis on their OUD treatment. Conclusion Past-month cannabis use was not associated with more or less opioid use during treatment. For patients who use cannabis, we identified specific characteristics of cannabis use associated with differential outcomes. Further examination of characteristics and patterns of cannabis use is warranted and may inform more tailored assessments and treatment recommendations.